2012
DOI: 10.1002/jssc.201100769
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultra‐performance liquid chromatography coupled with mass spectrometry to metabonomic study on spontaneously hypertensive rats and intervention effects of Ping Gan prescription

Abstract: This study describes the metabonomic characters of the spontaneously hypertensive rats (SHR) and intervention effects of Ping Gan prescription. Ultra performance LC coupled with Q-TOF MS (UPLC/MS-Q-TOF) was employed to develop a metabonomic method of the plasma of SHR. There was a significant difference in metabolic profiling observed between predose group of Wistar Kyoto rats and model group (SHR) by using the principal components analysis (PCA). Some significant changes in metabolites such as LysoPC(22:6), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Several metabolomic studies have been published that investigate the metabolic effects of hypertension [5][7]. These studies reported abnormalities in gender-linked steroid patterns [5] or lipid metabolism [6], [7]. Hypertension and its underlying pathophysiology may be present for years before clinical diagnosis, at which time irreversible pathology has already occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Several metabolomic studies have been published that investigate the metabolic effects of hypertension [5][7]. These studies reported abnormalities in gender-linked steroid patterns [5] or lipid metabolism [6], [7]. Hypertension and its underlying pathophysiology may be present for years before clinical diagnosis, at which time irreversible pathology has already occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical changes supporting the intervention effect of Ping Gan prescription for spontaneous hypertension treatment were reported to be associated with disturbance in the sphingolipid and fat metabolisms [83].…”
Section: Assessing and Exploring The Mechanisms Of The Therapeutic Efmentioning
confidence: 98%
“…UHPLC-MS-based metabolomics is increasingly used in the evaluation of TCMs [45,79,80]. Metabolomics seeks to elucidate the therapeutic properties and metabolism of prescription drugs and the metabolic pathways involved [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Characteristic fragmentation behaviors allow identification or tentative characterization of the chemical constituents in TCMs. Recently, chromatographic fingerprinting of the components by UHPLC-MS has become a powerful, widely-used technique to analyze TCMs, because it could systematically profile the composition of samples [45,46].…”
Section: Uhplc-ms Approach In Tcmmentioning
confidence: 99%